Pengembangan program pendidikan guru pendidikan teknologi dan kejuruan trans-nasional - Dadang Hidayat Martawijaya (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2011)
DEVELOPMENT OF EDUCATIONAL TEACHER EDUCATION TECHNOLOGY AND TRANS-NATIONAL VOCATIONAL EDUCATION PROGRAMRapid changes of science within a global dynamic changes requires adaptable educational program. Vocational Education Institutions neeD to develop program to enable students being competence. Trans-national perspective in preparing vocational teacher has been developed to solve share problems that are facing based on the PP.19/2005 initiating that teacher qualification is D-JV or 8-1. In addition, they have to qualify in pedagogical competent, personal characteristics, social and professional competence. Trans-national teacher education class consists of students who come from different places in Indonesia. The students are customized to have nationalism and have ability to compete in a global arena.